The mirage of a space between nature and nurture - Keller, Evelyn Fox, 1936- (e-Duke books scholarly collection., 2010)
Prominent historian of science considers how the opposition between nature (understood to be genetic or innate) and nurture (understood as acquired or environmental) came to be such an entrenched part of scientific and social ways of thinking.